TWI1 regulates cell‐to‐cell movement of OSH15 to control leaf cell fate. Issue 1 (27th August 2018) - Cui, Xuean; Zhang, Zhiguo; Wang, Yanwei; Wu, Jinxia; Han, Xiao; Gu, Xiaofeng; Lu, Tiegang
Summary: Cell pattern formation in plant leaves has attracted much attention from both plant biologists and breeders. However, in rice, the molecular mechanism remains unclear. Here, we describe the isolation and functional characterization of TWISTED‐LEAF1 ( TWI1 ), a critical gene involved in the development of the mestome sheath, vascular bundle sheath, interveinal mesophyll and sclerenchyma in rice leaves. Mutant twi1 plants have twisted leaves which might be caused by the compromised development and disordered patterning of bundle sheath, sclerenchyma and interveinal mesophyll cells. Expression of TWI1 can functionally rescue these mutant phenotypes. TWI1 encodes a transcription factor binding protein that interacts with OSH15, a class I KNOTTED1‐like homeobox (KNOX) transcription factor. The cell‐to‐cell trafficking of OSH15 is restricted through its interaction with TWI1. Knockout or knockdown of OSH15 in twi1 rescues the twisted leaf phenotype. These studies reveal a key factor controlling cell pattern formation in rice leaves.